Cigarette smoke-mediated oxidative stress induces apoptosis via the MAPKs/STAT1 pathway in mouse lung fibroblasts. Issue 1 (5th January 2016) - Lee, Hanbyeol; Park, Jeong-Ran; Kim, Eun-Jeong; Kim, Woo Jin; Hong, Seok-Ho; Park, Sung-Min; Yang, Se-Ran
Highlights: CSE decreased the proliferation of mouse lung fibroblasts, which is essential for the maintenance of extracellular matrix. CSE caused an abnormal inflammatory response and ROS/RNS-mediated stress by an imbalance in the cellular antioxidant defense system (GSH recycling and SOD activity), leading to the apoptosis of lung parenchymal fibroblasts. The apoptosis of lung fibroblasts, through the phosphorylation of STAT1 at Tyr701/Ser727 and the up-regulation of the MAPK pathway by CSE, contributes to the pathogenesis of COPD. Abstract: Cigarette smoking is the major aetiologic factor in chronic obstructive pulmonary disease (COPD). Lung fibroblasts are key participants in the maintenance of the extracellular matrix within the lung parenchyma. However, it still remains unknown how pulmonary fibroblasts are affected by cigarette smoking. Therefore, in this study, we isolated lung fibroblasts from mice and determined the apoptotic mechanism in response to cigarette smoke extract (CSE). When the lung fibroblasts were exposed to CSE, the generation of ROS was increased as shown by H2-DCFDA staining and Flow Cytometry. By immunocytochemistry, Ki67 expressing cells gradually decreased in a dose-dependent manner. The nitrite concentration in the supernatants increased, while the SOD activity and GSH recycling decreased in response to CSE. CSE increased the mRNA levels of TNF-α and COX-2, and the secretory proteins TNF-α and IL-6 increased as measured by ELISA. We next determined whether this inflammatory process is associated with the Bax/Bcl-2 apoptosis pathway. The Bax/Bcl-2 mRNA ratio increased, and cleaved caspase-3 protein was activated in the lung fibroblasts treated with CSE. Moreover, CSE induced the phosphorylation of STAT1 at Tyr701/Ser727 and increased the activation of ERK1/2, p38, and JNK in the MAPK pathway. Taken together, these data suggest that CSE-mediated inflammation alters the redox regulation via the MAPK-STAT1 pathway, leading to intrinsic apoptosis of lung fibroblasts.